The Effect Of Modernization Of Tax Administration System, Fiscus Services, Understanding Tax Regulations And Tax Sanctions On The Compliance Of Personal Taxpayers (Case Study On Employees Of Pt Arjuna Maha Sentosa) - Amelia Suci Wulandari; Limajatini Limajatini (Global Accounting, 2022)
This study aims to analyze the modernization of the tax administration system, fiscus services, understanding of tax regulations, and tax sanctions on individual taxpayer compliance through case studies on employees of PT Arjuna Maha Sentosa. This research uses quantitative methods and survey research. The population in this study were employees of PT Arjuna Maha Sentosa. The sampling technique in this study used simple random sampling and obtained a sample of 70 respondents. The data analysis technique uses multiple linear regression and data processing using the SPSS version 26 program. The results show that partially modernization of the tax administration system and understanding of tax regulations have a significant effect on individual taxpayer compliance, while the fiscus services and tax sanctions have no effect on individual taxpayer compliance. Simultaneously all independent variables affect individual taxpayer compliance.